2006
DOI: 10.2105/ajph.2005.062745
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cigarette Smoking With HIV Prognosis Among Women in the HAART Era: A Report From the Women’s Interagency HIV Study

Abstract: Some of the benefits provided by HAART are negated in cigarette smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
194
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(217 citation statements)
references
References 15 publications
19
194
4
Order By: Relevance
“…1 By contrast, between 50% and 70% of PLWHA smoke cigarettes daily. 3,5,[10][11][12][13] On a positive note, one longitudinal study showed that smoking rates may be declining among women with HIV (to 39% in 2011 in the Women's Interagency HIV Study). 14 Although the reasons for this high prevalence are not well understood, there are some factors that appear to distinguish nonsmoking from smoking PLWHA.…”
Section: Prevalence Of Smoking Cessation In Hivmentioning
confidence: 99%
See 1 more Smart Citation
“…1 By contrast, between 50% and 70% of PLWHA smoke cigarettes daily. 3,5,[10][11][12][13] On a positive note, one longitudinal study showed that smoking rates may be declining among women with HIV (to 39% in 2011 in the Women's Interagency HIV Study). 14 Although the reasons for this high prevalence are not well understood, there are some factors that appear to distinguish nonsmoking from smoking PLWHA.…”
Section: Prevalence Of Smoking Cessation In Hivmentioning
confidence: 99%
“…21 HIV+ smokers also have lower CD4 cell counts, higher HIV viral loads, and lower self-reported quality of life than HIV+ nonsmokers. [19][20][21][22] Smokers are also more likely to progress to an AIDS diagnosis, 23 have poorer response to ART, 12 and are more likely to be nonadherent to ART. 24 Importantly, longer duration of abstinence from smoking substantially reduces HIV symptom burden.…”
Section: Smoking-related Morbidity and Mortality Among Plwhamentioning
confidence: 99%
“…Compared with the 20% prevalence of smoking in the United States general population (1), the prevalence of smoking has consistently been reported as higher in HIV-infected populations (Table 1) (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). In numerous studies of smoking prevalence conducted in varied risk groups from the United States and Europe, more than two thirds of HIV-infected persons have reported being a regular smoker at some time in their life.…”
Section: Cigarette Smoking Among Hiv-infected Personsmentioning
confidence: 99%
“…Studies have suggested that cigarette smoking is associated with poorer virological and immunological responses to HAART and this may explain, at least partly, why patients on HAART have an ongoing increased risk of pneumonia [34,49,50]. Furthermore, smoking may also accelerate the progression to AIDS [49,51].…”
Section: Risk Factorsmentioning
confidence: 99%